Subcritical carbon dioxide extraction of stereospermum fimbriatum’s stem bark and the extract’s potential as an anti-dermal infection agent - Awang, Anis Fadhlina Izyani; Sarker, Md. Zaidul Islam; Ahmed, Qamar Uddin; Md. Jaffri, Juliana; Omar, Muhammad Nor (2016)
Dermal infection is one of the most common infections that occur worldwide. The problem of antibiotic resistant and its adverse effect on the host have also worsened the issue, and this has urge scientists to find new effective drugs. Earth is enriched with natural resources such as plants that have been used traditionally to cure diseases. Stereospermum fimbriatum or